Eficiencia y eficacia del teletrabajo durante la pandemia COVID-19 en el Gobierno Autónomo Descentralizado Municipal del cantón Tosagua - Martínez Parra, Raúl Mijail (2022)
The objective of this research was to evaluate the efficiency and effectiveness of teleworking during the COVID-19 pandemic in the Municipal Autonomous Decentralized Government in Tosagua canton in 2021. The methodological strategy responds to descriptive and documentary field research, systematized with deductive methods. and inductive, through survey and interview techniques. The results showed nonconformity in the users, due to disorganization and operational problems caused by teleworking, such as lack of rules and regulations that regulate the online modality, delay in the technological system and poor professional training. In conclusion, an action plan with administrative management strategies will strengthen quality and officials will execute public resources in accordance with good practices of public administration.